Research on folding suspension of multi-constrained rover based on the variation and fusion of rods and pairs. (24th August 2017) - Yang, Fei; Yue, Honghao; Li, Meng; Tao, Jianguo; Deng, Zongquan
Planetary rovers with folding functions can solve the contradiction between the limited space of the vehicle and the functional diversity of the rover and greatly improve the efficiency–cost ratio of space launch activities. In this article, the multi-constrained quadrilateral suspension is considered based on the practical requirements of planetary detection. Based on graph theory and metamorphic theory, the structural characteristics and movement patterns of the rover are analyzed, the configuration transforming process of adding or decreasing the number of rods and kinematic pairs during folding is studied, and the corresponding mathematical model is established. The suspension of the rover is divided into three basic units, and the folding study is performed around each unit. The folding set of each unit type is given, and a feasible folding set is selected for each type of unit according to their structural characteristics and constraint conditions. At the same time, 15-folding schemes for the rover are given, and the optimal scheme is determined. According to the final folding scheme of the rover, the principle prototype of the rover is developed, and the functional experiment of the folding and unfolding is performed. The experimental results verify the feasibility and rationality of the folding scheme, indicating that the developed detection vehicle has a large fold ratio, which can fully adapt to the limited space inside the rocket. The theoretical and technical results can provide technical support for the engineering application of subsequent rovers with folding.